Compartmentalized Cerebral Metabolism of [1,6-13C]Glucose Determined by in vivo13C NMR Spectroscopy at 14.1 T - Duarte, João M.; Lanz, Bernard; Gruetter, Rolf (Frontiers in Neuroenergetics, 2011)
Cerebral metabolism is compartmentalised between neurons and glia. Although glial glycolysis is thought to largely sustain the energetic requirements of neurotransmission while oxidative metabolism takes place mainly in neurons, this hypothesis is matter of debate. The compartmentalization of cerebral metabolic fluxes can be determined by 13C NMR spectroscopy upon infusion of 13C-enriched compounds, especially glucose. Rats under light α-chloralose anaesthesia were infused with [1,6-13C]glucose and 13C enrichment in the brain metabolites was measured by 13C NMR spectroscopy with high sensitivity and spectral resolution at 14.1 T. This allowed determining 13C enrichment curves of amino acid carbons with high reproducibility and to reliably estimate cerebral metabolic fluxes (mean error of 8%). We further found that TCA cycle intermediates are not required for flux determination in mathematical models of brain metabolism. Neuronal tricarboxylic acid cycle rate (VTCA) and neurotransmission rate (VNT) were 0.45±0.01 and 0.11±0.01 µmol/g/min, respectively. Glial VTCA was found to be for 38±3% of total cerebral oxidative metabolism, accounting for more than half of neuronal oxidative metabolism. Furthermore, glial anaplerotic pyruvate carboxylation rate (VPC) was 0.069±0.004 µmol/g/min, i.e. 25±1% of the glial TCA cycle rate. These results support a role of glial cells as active partners of neurons during synaptic transmission beyond glycolytic metabolism.